2014
DOI: 10.1088/0004-637x/786/1/74
|View full text |Cite
|
Sign up to set email alerts
|

Segue 1: An Unevolved Fossil Galaxy From the Early Universe

Abstract: We present Magellan/MIKE and Keck/HIRES high-resolution spectra of six red giant stars in the dwarf galaxy Segue 1. Including one additional Segue 1 star observed by Norris et al., high-resolution spectra have now been obtained for every red giant in Segue 1. Remarkably, three of these seven stars have metallicities below [Fe/H] = −3.5, suggesting that Segue 1 is the least chemically evolved galaxy known. We confirm previous medium-resolution analyses demonstrating that Segue 1 stars span a metallicity range o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
266
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(291 citation statements)
references
References 115 publications
(259 reference statements)
23
266
2
Order By: Relevance
“…Other local galaxies with at least one such star are Draco (Shetrone et al 2001;Fulbright et al 2004;Cohen & Huang 2009), Sagittarius (Zaggia et al 2004;Bonifacio et al 2006;Sbordone et al 2015;and Monaco et al, in prep. ), Fornax (Tafelmeyer et al 2010), Ursa Minor (Kirby & Cohen 2012;Ural et al 2015), Sextans (Aoki et al 2009b;Tafelmeyer et al 2010), Coma Ber (Frebel et al 2010b), Ursa Maior II (Frebel et al 2010b), Segue 1 (Roederer & Kirby 2014;Frebel et al 2014), Hercules (Koch et al 2008;Adén et al 2011), Boo I (Gilmore et al 2013;Ishigaki et al 2014b), and Boo II (Koch & Rich 2014). Particularly relevant to the present discussion is the discovery of a CEMP-no star in the Sculptor dwarf spheroidal (Skúladóttir et al 2015).…”
Section: Low Scatter In the Iron-to-calcium Ratiomentioning
confidence: 84%
“…Other local galaxies with at least one such star are Draco (Shetrone et al 2001;Fulbright et al 2004;Cohen & Huang 2009), Sagittarius (Zaggia et al 2004;Bonifacio et al 2006;Sbordone et al 2015;and Monaco et al, in prep. ), Fornax (Tafelmeyer et al 2010), Ursa Minor (Kirby & Cohen 2012;Ural et al 2015), Sextans (Aoki et al 2009b;Tafelmeyer et al 2010), Coma Ber (Frebel et al 2010b), Ursa Maior II (Frebel et al 2010b), Segue 1 (Roederer & Kirby 2014;Frebel et al 2014), Hercules (Koch et al 2008;Adén et al 2011), Boo I (Gilmore et al 2013;Ishigaki et al 2014b), and Boo II (Koch & Rich 2014). Particularly relevant to the present discussion is the discovery of a CEMP-no star in the Sculptor dwarf spheroidal (Skúladóttir et al 2015).…”
Section: Low Scatter In the Iron-to-calcium Ratiomentioning
confidence: 84%
“…We do not consider Sagitarius, since this galaxy has been shown to be considerably tidally disrupted (Ibata et al 1995;Mateo et al 1996;Majewski et al 2003), and its mass is therefore very uncertain. Table 1 shows the V-band luminosities, L V , the velocity dispersions, σ, and the half light radii, r 1/2 taken from Walker et al (2009Walker et al ( , 2015, and the average Fe and Eu abundances (Shetrone et al 2001(Shetrone et al , 2003Frebel et al 2010;Letarte et al 2010;Frebel et al 2014;Ji et al 2016a,b;Roederer & Kirby 2014;Tsujimoto et al 2015;Roederer et al 2016). The errors of the average abundances shown in …”
Section: The Galaxy Samplementioning
confidence: 99%
“…Recently, Ji et al (2016a) and Roederer et al (2016) reported the first discovery of highly r-process enriched stars in a UFD, Reticulum II, while there are only strong upper limits on the abundances of r-process elements for some other UFDs (Frebel et al 2010(Frebel et al , 2014Roederer & Kirby 2014). These measurements that show large fluctuations in the r-process abundance imply that only a single r-process event took place in Reticulum II.…”
Section: Introductionmentioning
confidence: 99%
“…We used the compilation of line lists by Frebel et al (2014), based on lines from Aoki et al (2002), Barklem et al (2005), Lawler et al (2009), and the VALD database (Kupka et al 1999). The neutron-capture absorption lines in the blue spectral region, particularly close to strong CH or CN features, need to be carefully synthesized, since these are intrinsically weak in CEMP-no stars.…”
Section: Neutron-capture Elementsmentioning
confidence: 99%